Penerapan Teknik Relaksasi Otot Progresif dan Hidroterapi pada Lansia dengan Hipertensi Diposyandu Lansia Desa Karangbanjar Bojongsari - Berlan Sendi Nugroho; Mariah Ulfah; Wasis Eko Kurniawan (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hypertension, commonly known as high blood pressure, is a condition where blood pressure in the blood vessels consistently exceeds the normal range of 140/90 mmHg. Central Java Province has the highest prevalence of hypertension in Indonesia, at 13.4%. In 2020, Purbalingga Regency reported 268,936 cases of hypertension. According to data from the Bojongsari Health Center, there were 11,596 hypertension patients in 2023. Among the 13 villages in Bojongsari District, there are villages that have experienced an increase in hypertension cases of over 20% annually, one of which is Karangbanjar Village, with 542 cases of hypertension in 2022 and an increase to 858 cases (26%) in 2023. Hypertension treatment can be done through complementary therapy such as progressive muscle relaxation therapy and hydrotherapy. This Community Service Program (PkM) was attended by 20 participants. The results from the pre-test to the post-test showed an increase in the average score, from 59 to 81.5. The evaluation of participants' skills indicated an improvement, with 90% in the “good” category and 10% in the “adequate” category. In addition, there was a significant change in participants' blood pressure after receiving therapy. This activity was carried out using lectures and discussions, with PowerPoint presentations, leaflets, and videos demonstrating how to perform progressive muscle relaxation therapy and hydrotherapy. This educational activity showed an increase in knowledge among the elderly in performing progressive muscle relaxation therapy and hydrotherapy to reduce hypertension.